2013
DOI: 10.1136/bcr-2013-201179
|View full text |Cite
|
Sign up to set email alerts
|

Massive breast necrosis after extravasation of a full anthracycline cycle

Abstract: A 57-year-old woman with invasive breast cancer was referred for adjuvant chemotherapy after undergoing breast conservative therapy and axillary dissection. A port was inserted in the contralateral subclavian vein and epirubicin, cyclophosphamide and 5-fluorouracil was the treatment of choice. After the first cycle, the patient was sent home. The following day, she reported rapidly developing redness and pain in the right breast and diagnosis of epirubicin extravasation was made. She was hospitalised, the port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
7
0
4
Order By: Relevance
“…Extravasation injury is rarer with central administration than peripheral routes [6] however, central venous devices such as Port-a-Cath have shown extravasation rates of up to 6% in the literature [ 4 , 7 ]. There have been several reports of extravasation with the use of central venous access devices with rates from 0.26% to 4.7% [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extravasation injury is rarer with central administration than peripheral routes [6] however, central venous devices such as Port-a-Cath have shown extravasation rates of up to 6% in the literature [ 4 , 7 ]. There have been several reports of extravasation with the use of central venous access devices with rates from 0.26% to 4.7% [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multi-center studies have shown that surgical treatment is the last resort, as timely treatment can prevent surgery in a large proportion of patients if intravenous infusion of dexrazoxane is given within 6 hours of the extravasation incident [15] . If the port removal is delayed, surgical management such as debridement and flap coverage may be required to manage the necrotic area [ 8 , 9 ]. Innovative techniques such as vacuum-sealing have also been described in the literature as per the case herein reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the reported case, the VAC system was used as a bridge to reconstructive surgery with a latissimus dorsi flap. Vasconcelos et al (5) reported in 2013 a delayed breast reconstruction with deep inferior epigastric perforator flap for a patient with breast cancer, 8 months after an epirubicin port-extravasation injury. Wilson et al (6) reported a microvascular free flap reconstruction with a lateral arm flap from the right arm to cover an epirubicin-induced defect of the antecubital fossa.…”
Section: Discussionmentioning
confidence: 99%
“…There is one report of massive breast necrosis due to extravasation of anthracycline in a patient with breast cancer . Chemotherapy was administered through a port inserted in contralateral subclavian vein.…”
Section: Discussionmentioning
confidence: 99%